Endothelial vasoactive function in children and adolescents with obesity and metabolic syndrome - V. V. Bekezin; L. V. Kozlova; V. A. Milyagin; I. S. Kozlova (Российский кардиологический журнал)
Endothelial vasoactive function was assessed in 66 children and adolescents aged 11-16 years, with obesity and metabolic syndrome (MS). Pathological result of rheovasography stress test was observed in 71,4% of MS children, pointing to endothelial dysfunction (ED) presence. In MS children, vasoconstriction was identified more often than in obese children -by 1, 77 times (p < 0,05). Therefore, there is a need for early ED correction in MS children.